TO THE QUESTION ABOUT THE FORMATION OF OZONE HOLES IN THE ATMOSPHERE AND THE PRESENCE OF THE AREAS WITH THE LOWEST VALUES OF TEMPERATURE - Ivin, V. F. (Science and Transport Progress, 2008)
The article represents the new theoretical model of formation of ozone holes in atmosphere of the Earth and areas with the lowest values of air temperature and the forecasts concerning change of climatic conditions on the Earth in the future.